Operationalizing Sustainable Development Goals in Vulnerable Coastal Areas of Ecuador and Pakistan: Marginalizing Human Development?. Issue 4 (2nd October 2019) - Waldmüller, Johannes M.; Jamali, Hameed; Nogales, Nelson
Abstract: Drawing on multi-sited ethnographic fieldwork in socially and ecologically vulnerable coastal areas of Ecuador and Pakistan, we focus on Chinese-funded investment projects to analyze how SDGs are susceptible to be instrumentalized in the context of exploitative economic dependencies, as well as national development agendas. In our case studies, forced displacement of vulnerable inhabitants during the post-earthquake recovery in coastal Ecuador and displacement of small-scale fishers in coastal Pakistan are justified by SDG implementation. We identify a techno-managerial approach to SDGs in order to discuss its effects in terms of endangering ecosystems and human freedoms, increased social vulnerability and dependence on wage labour. Despite contextual differences, both case studies reveal a similar pattern of intervention under the pretext of SDGs where human freedoms and capabilities are severely undermined by large-scale projects of territorial and social securitization.